Pemodelan dan Estimasi Sumberdaya Nikel Laterit Berdasarkan Kandungan Ni dan Fe dengan Menggunakan Metode Kriging di PT Putra Perkasa Abadi, Kecamatan Langgikima, Kabupaten Konawe Utara, Provinsi Sulawesi Tenggara - Muhamad Rizaldi Fadlilah; Noor Fauzi Isniarno; Dono Guntoro (UNISBA Press, 2023)
Abstract. Nickel laterite is a metallic mineral resulting from the chemical weathering process of ultramafic rocks which results in residual and secondary enrichment of Ni, Fe, Mn, and Co elements (Syafrizal et al.,2011). With the cut-off grade Ni, modeling and estimation of resources is important to obtain a block model of Ni resources. The distribution of Ni levels is heterogeneous, so mining is carried out by selective mining referring to model blocks that have been mapped to meet the cut-off grade Ni. Based on this, it is possible for low and high Ni levels to be optimized, because if you only take Ni levels above 1.6%, Ni levels below the cut-off grade are not utilized. The resource estimation method used is kriging. Because kriging is the best linear unbiased estimator, many parameters are considered in kriging one of which is the variogram model. The variogram model is a geostatistical analysis by considering the location of the sample point, so that information on the relationship of one point with another point is expressed in the range/radius of information points that still have a spatial relationship. Based on statistical analysis, Block North and Block South data distribution are abnormal, with coefficient of variation values of 0.494 and 0.410. Resources that meet the cut-off grade Ni for blending needs are obtained low nickel, medium and high grade ore nickel. The total laterite nickel resources of the North Block amounted to 36,757 tons with an average Ni content of 1.64%, the total laterite nickel resources of the South Block amounted to 178,186 tons with an average Ni content of 1.62%. When viewed from the average rate per block, both blocks meet the cut-off grade Ni. Abstrak. Nikel laterit merupakan mineral logam hasil proses pelapukan kimia batuan ultramafik yang mengakibatkan pengkayaan unsur Ni, Fe, Mn, dan Co secara residual dan sekunder (Syafrizal et al., 2011). Dengan adanya cut-off grade Ni, maka pemodelan dan estimasi sumberdaya penting dilakukan untuk mendapatkan model blok sumberdaya Ni. Distribusi kadar Ni yang heterogen, maka penambangan dilakukan secara selective mining mengacu pada blok model yang sudah dipetakan untuk memenuhi cut-off grade Ni. Berdasarkan hal tersebut, memungkinkan adanya kadar Ni rendah dan tinggi yang harus di-optimalkan, karena jika hanya mengambil kadar Ni diatas 1.6%, kadar Ni di bawah cut-off grade tidak termanfaatkan. Metode estimasi sumberdaya yang digunakan adalah kriging. Pemilihan metode kriging dikarenakan kriging merupakan best linear unbiased estimator, banyak parameter yang diperhatikan dalam kriging salah satunya adalah model variogram. Model variogram merupakan analisis geostatistik dengan mempertimbangkan lokasi titik sampel, sehingga didapatkan informasi hubungan satu titik dengan titik yang lainnya dinyatakan dalam range/radius titik informasi yang masih memiliki hubungan secara spasial. Berdasarkan analisis statistik, Blok North dan Blok South distribusi datanya tidak normal, dengan nilai koefisien variasi 0.494 dan 0.410. Sumberdaya yang memenuhi cut-off grade Ni untuk kebutuhan blending didapatkan low nickel, medium dan high grade ore nickel. Total sumberdaya nikel laterit Blok North sebesar 36,757 ton dengan kadar Ni rata-rata 1.64%, total sumberdaya nikel laterit Blok South sebesar 178,186 ton dengan kadar Ni rata-rata 1.62%. Jika dilihat dari kadar rata-rata per-Blok, kedua Blok memenuhi cut-off grade Ni.